Pemilihan Moda Angkutan Barang Menggunakan Analisis AHP: Selection Of Goods Transport Modes Using AHP Analysis - Nur Halik, Dadang; Hakzah; Widarto, Hendro (Media Ilmiah Teknik Sipil, 2025)
Enrekang is a producer and contributor of diverse and abundant agricultural commodities, distributed both within and outside the region using various types of goods transportation modes. This research aims to determine the characteristics of commodities and the choice of goods transportation modes. The research method is descriptive quantitative and data is obtained from surveys and interviews with 150 respondents of freight transport drivers, data analysis uses the Analytical Hierarchy process (AHP). The results show that the characteristics of departure time are dominant during the day at 14.00 - 16.00 WITA, at night 20.00 - 22.00 WITA, while the arrival time at the distribution location during the day is dominant at 06.00 - 08.00 WITA, and at night 02.00 - 04.00 WITA. The distribution of commodities within South Sulawesi Province is dominant to Parepare City and outside the region to West Sulawesi. The choice of efficient goods transportation mode used in the process of distributing agricultural commodity results shows that the 3 axle truck mode has a priority weight of 0.43%.